P PEMETAAN KAWASAN RAWAN BANJIR DAN STRATEGI PENGELOLAAN LAHAN PERTANIAN DI KOTA PALOPO - Hidayat, Wahyu; Syafruddin, Syafruddin (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2025)
The research on flood-prone areas based on Geographic Information Systems (GIS) for disaster mitigation efforts is crucial due to the rapid and irregular development in the suburban areas, which leads to cities becoming prone to disasters. The objective of this study is to determine the extent of flood-prone areas through flood vulnerability mapping, in order to optimize flood impact mitigation efforts on Sustainable Agricultural Land in Palopo City. The research location is Palopo City. The research method used is the scoring and overlay method on 6 parameters for 5 categories of flood vulnerability. The analysis results of flood-prone areas in Palopo City show a flood vulnerability map with the following area classifications: vulnerable (16,725.33 ha), fairly safe (7,864.23 ha), moderately vulnerable (2,158.49 ha), safe (924.03 ha), and very vulnerable (71.92 ha). The generated map provides information about flood-prone areas to the Palopo City government, especially the Regional Disaster Management Agency and the Agriculture, Livestock, and Plantation Department of Palopo City